2012
DOI: 10.1088/0268-1242/28/1/015018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spin lifetimes inn-Ge characterized between three-terminal and four-terminal nonlocal Hanle measurements

Abstract: We compared the temperature dependence of spin lifetime in n-Ge characterized from three-terminal (3T) and four-terminal (4T) Hanle measurements using single-crystalline Fe/MgO/n-Ge tunnel junctions. The bias conditions of the two schemes were chosen to be about the same in order to compare the spin lifetimes (τ 3T and τ 4T ). The temperature dependences of τ 3T and τ 4T behave in a very similar way at the low temperature region (T 10 K), and both τ 3T and τ 4T decrease as the temperature increases, which is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
47
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 37 publications
4
47
2
Order By: Relevance
“…However, the donor-driven spin relaxation mechanism discussed above holds also for the interface spin relaxation, if the scattering centers at the interface allow for scattering between two valleys residing on different crystallographic axes. From spin transport experiments, the Elliott-Yafet mechanism was reported to be dominant in highly doped n-Ge, but the data range was only up to 100 K [14,15], with no correlation of τ n-Ge with temperature in the range from 150 to 225 K [16]. Thus, we cover the important range from 130 K to RT and provide experimental evidence for an impurity-driven spin relaxation mechanism in highly doped n-Ge.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 78%
See 1 more Smart Citation
“…However, the donor-driven spin relaxation mechanism discussed above holds also for the interface spin relaxation, if the scattering centers at the interface allow for scattering between two valleys residing on different crystallographic axes. From spin transport experiments, the Elliott-Yafet mechanism was reported to be dominant in highly doped n-Ge, but the data range was only up to 100 K [14,15], with no correlation of τ n-Ge with temperature in the range from 150 to 225 K [16]. Thus, we cover the important range from 130 K to RT and provide experimental evidence for an impurity-driven spin relaxation mechanism in highly doped n-Ge.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 78%
“…Moreover, spin injection and spin relaxation in Ge have been extensively studied using electron spin resonance [4][5][6][7][8][9] and optical techniques [10][11][12][13]. However, in spite of all the recent progress in the Ge field and in contrast to Si, spin transport in Ge using nonlocal four-terminal techniques has only been observed at low temperatures to date [14][15][16]. Spin transport has been reported through a Ni/Ge/AlGaAs junction; however, optical spin injection lacks the scalability needed for nanoelectronic applications [17].…”
mentioning
confidence: 99%
“…Moreover, spin injection and spin relaxation in Ge have been extensively studied using electron spin resonance [20][21][22][23][24][25] and optical techniques [26][27][28][29]. However, in spite of all the recent progress in the Ge field and in contrast to Si, spin transport in Ge using nonlocal four-terminal techniques has only been observed at low temperatures to date [30][31][32]. Spin transport has been reported through a Ni/Ge/AlGaAs [8,9] spin lifetime (non-local Hanle) (ns) [10] spin lifetime (ESR) (ns) [11][12][13] 10 n 0.3 10 300 300 n 0.3 1 8.5 300 p 0.27 -- Figure 3 Proposed spin field effect transistor (Spin FET) device, after Datta and Das [5].…”
mentioning
confidence: 99%
“…Some electrical studies [31,34,35] reported spin injection into highly doped n-Ge at room temperature (RT), raising the possibility that RT Ge spintronics can be realised. Unfortunately, these studies used a three-terminal method, the reliability of which is now being called into question.…”
mentioning
confidence: 99%
“…Spin injection was demonstrated in Ge by using tunnel contacts [14][15][16] and Schottky contacts. 17 Mn 5 Ge 3 is a ferromagnet (FM) with a Curie temperature T C  300 K 18,22 that can be enhanced by C-doping up to T C = 450 K. [19][20][21] Cdoped Mn 5 Ge 3 C x has a negligible conductivity mismatch with highly doped Ge 22 , which makes it particularly interesting as a contact material for spin injection into Ge.…”
mentioning
confidence: 99%